The Writing Teacher’s Second Self: Theory and Practice of Responding to Student Writing - Mayo, Wendell (Kalbotyra, 2002)
Although rhetorical theorists such as N. Sommers (1988), C. H. Knoblauch and L. Brannon (1984), and E. M. White (1984) suggest that writing teachers insinuate clear and helpful readerpersonae in the written comments they make on student writing, this article focuses on students’ impressions of such personae. The research employs A. A. Lunsford’s (1992) key topoi of teachers’ commentary on student writing in the United States, analysis of marked student essays, and interviews of student-authors to ascertain the relationships among the types of comments teachers make, the impressions these comments make on students, and their impact on students’ strategies for revising their writing. Results suggest that teachers’ comments in the third person impersonal paint of view, on form, and in the declarative or imperative modes suggest a ‘teacherly’ persona and students are more willing to adopt the comment and revise the text in question. Comments in the first person, on content, and in the interrogative mode suggest a ‘writerly’ persona, one that reinforces students’ identities as ‘writers’, though they are less likely to revise the text.